Forensics in telecommunications, information, and multimedia Third International ICST Conference, e-Forensics 2010, Shanghai, China, November 11-12, 2010, Revised Selected Papers - International ICST Conference on Forensic Applications and Techniques in Telecommunications, Information and Multimedia 2010 Shanghai, China); Lai, Xuejia; Gu, Dawu.; Jin, Bo.; Wang, Yongquan; Li, Hui.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International ICST Conference on Forensic Applications and Techniques in Telecommunications, Information and Multimedia, E-Forensics 2010, held in Shanghai, China, in November 2010. The 32 revised full papers presented were carefully reviewed and selected from 42 submissions in total. These, along with 5 papers from a collocated workshop of E-Forensics Law, cover a wide range of topics including digital evidence handling, data carving, records tracing, device forensics, data tamper identification, and mobile device locating.
Electronic reproduction.
Keywords: Computer crimes -- Investigation -- Congresses; Telecommunication systems -- Security measures -- Congresses; Electronic books